Scenic routes around the world [videorecording (DVD)] (Questar, 2011)
Features footage of some of the world's most exotic and beautiful roads, rivers, and trails filmed in high definition and spanning six continents, from to Europe, Alaska, Africa, the Amazon, and beyond, and introduces people along the way who share the ancient customs that have been preserved for centuries.